Integration of Bio-Enzyme-Treated Super-Wood and AIE-Based Nonwoven Fabric for Efficient Evaporating the Wastewater with High Concentration of Ammonia Nitrogen - Qian Ding; Bingqi Jin; Yinxia Zheng; Huiru Zhao; Jun Wang; Haoxuan Li; Dong Wang; Ben Zhong Tang (Nano-Micro Letters)
Highlights Bio-enzyme-treated super-wood and aggregation-induced emission (AIE)-based nonwoven fabric is integrated into a solar evaporator. The evaporator demonstrates a high evaporation rate of 12.83 kg m−2 h−1 when treating simulated wastewater containing 30 wt% NH4Cl under 1.0 sun of illumination. AIE-doped evaporator exhibits remarkable photodynamic antibacterial activity against mildew and bacteria.